Pengaruh Employee Engagement, Iklim Organisasi, Dan Kemampuan Kerja Terhadap Produktivitas Karyawan (Studi Kasus Pada Karyawan UMKM Tahu Kres KWB) - Rachma Rizki Puspita Ismara; Eka Farida; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This studi aims to determine the effect of employee engagament, organizational climate, and ability work on work produkctivity at UMKM Tahu Kres KWB. The sample used in this study were 31 employee by using saturated sample technique. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis. Testing the data used is simultaneous hypothesis testing (Test F) and partial hypothesis testing (Test t). The result showed that simultsneously (Test F) the variables of employee engagament, organizational climate, and ability work significant effect on employee productivity at UMKM Tahu Kres KWB. When, based on partial test results (Test t) the variables of employee engagament significant effect on employee productivity at UMKM Tahu Kres KWB, variables organizational climate no significant effect on employee productivity at UMKM Tahu Kres KWB, and variables ability work significant effect on employee productivity at UMKM Tahu Kres KWB. Keywords: Employee Engagement, Organizational Climate, Ability Work and Productivity Employee